2012
DOI: 10.1128/jcm.06599-11
|View full text |Cite
|
Sign up to set email alerts
|

Molecular and Culture-Based Assessment of the Microbial Diversity of Diabetic Chronic Foot Wounds and Contralateral Skin Sites

Abstract: Wound debridement samples and contralateral (healthy) skin swabs acquired from 26 patients attending a specialist foot clinic were analyzed by differential isolation and eubacterium-specific PCR-denaturing gradient gel electrophoresis (DGGE) in conjunction with DNA sequencing. Thirteen of 26 wounds harbored pathogens according to culture analyses, with Staphylococcus aureus being the most common (13/13). Candida (1/13), pseudomonas (1/13), and streptococcus (7/13) were less prevalent. Contralateral skin was as… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
51
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 59 publications
(53 citation statements)
references
References 43 publications
2
51
0
Order By: Relevance
“…Wound infection is commonly defined according to the presence of pathogens and colonization densities exceeding ≥106 organisms per gram of tissue and the development of significant tissue damage and clinical signs of infection. 12,13 In the present study, 50 patients were studied for over a period of 18 months. The demographics and patient characteristics have been described in ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…Wound infection is commonly defined according to the presence of pathogens and colonization densities exceeding ≥106 organisms per gram of tissue and the development of significant tissue damage and clinical signs of infection. 12,13 In the present study, 50 patients were studied for over a period of 18 months. The demographics and patient characteristics have been described in ( Table 2).…”
Section: Discussionmentioning
confidence: 99%
“…In the past few years, however, molecular microbiology techniques have demonstrated the presence of greater numbers and varieties of species in various types of wounds than had previously been recognized. 24,28,29,[37][38][39] The goal now is to better understand the role of the many organisms we now know that comprise the cutaneous microbiota in DFU.…”
Section: Discussionmentioning
confidence: 99%
“…28 Defining the full microbiota of both intact and wounded skin should improve our understanding of the microbial nature of DFU. 29 …”
Section: Introductionmentioning
confidence: 99%
“…Routine analysis of wound specimen normally involves the use of traditional culture methods such as selective and differential agar media to culture the anaerobic and aerobic bacteria [4]. The organisms are classified by means of similarities and differences based on their phenotypic characteristics such as cell appearance, cell shape, size, pigmentation [11][12][13]. Gram staining, biochemical tests (catalase and oxidase) and controlled growth conditions are required for definitive grouping of bacteria [12].…”
Section: Introductionmentioning
confidence: 99%
“…However, with the aid of molecular diagnostic techniques, identification has shown that most chronic wounds are polymicrobial [11]. Culture-based techniques alone often fail to identify fastidious bacteria that are important in diagnosis and they may underestimate microbial diversity [11] while culture-independent methods are able to detect bacterial species that were omitted by culture-based techniques [16].…”
Section: Introductionmentioning
confidence: 99%